1981
DOI: 10.1113/jphysiol.1981.sp013682
|View full text |Cite
|
Sign up to set email alerts
|

Ionized calcium in milk and the integrity of the mammary epithelium in the goat.

Abstract: SUMMARY1. Injection of citrate or EGTA solutions into the lumen of the mammary gland of goats in quantities sufficient to reduce ionized calcium to less than one-tenth of normal, led to increases in milk concentrations of Na and Cl and decreases in K and lactose.2. Subsequent milk yields were decreased in glands treated with citrate but not in those treated with EGTA.3. Blood-milk potential difference decreased (i.e. towards zero) in glands in which citrate was present.4. In goats milked hourly with the aid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 15 publications
5
33
0
Order By: Relevance
“…The mammary epithelium is also a polarised epithelium and in the first experiment we confirmed that in mammary cells Ca sensitivity is indeed mediated only via the apical membrane. Moreover, we also confirmed earlier studies showing that extracellular Ca levels can influence TJ status (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. Thus, for PTHrP to have an effect on mammary TJs it would have to act on the apical side of the cell.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The mammary epithelium is also a polarised epithelium and in the first experiment we confirmed that in mammary cells Ca sensitivity is indeed mediated only via the apical membrane. Moreover, we also confirmed earlier studies showing that extracellular Ca levels can influence TJ status (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. Thus, for PTHrP to have an effect on mammary TJs it would have to act on the apical side of the cell.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, maintaining extracellular Ca levels, presumably to facilitate adequate intracellular levels of Ca, is a prerequisite for preventing mammary TJ breakdown in vitro and in vivo (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. The role of PTHrP in maintaining cellular Ca homeostasis and Ca transport in epithelia, including that of the mammary gland, is well recognised (Seitz et al 1993, Philbrick et al 1996, Friedman 2000, Lafond et al 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGTA injection has been shown to open mammary tight junctions in the lactating goat (Neville & Peaker 1981). If the tight junctions block the passage of [ 14 C]sucrose into the bloodstream of the lactating animal, then opening the tight junctions with EGTA should allow passage of the tracer.…”
Section: [ 14 C]sucrose Passage From Mammary Lumen To Blood During Prmentioning
confidence: 99%
“…Not surprisingly, the transport and handling of calcium by the mammary epithelium has received considerable attention because of its importance in the context of neonatal nutrition. An understanding of calcium transport by mammary secretory cells is also important in relation to the integrity of mammary tight junctions and the synthesis of milk components such as caseins [3][4][5]. In addition, the potential link between calcium and breast cancer has increased the interest in mammary calcium transport [6,7].…”
Section: Introductionmentioning
confidence: 99%